The Mechanism of Action of Cancer Therapeutic Vaccines and Their Application Prospects - Li, Mingrui (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The complexity of cancer as a global health problem has also led to the development of various novel therapeutics, including prophylactic vaccines. Scientific breakthroughs and technological developments have changed cancer research; since cancer is a complicated disease with many factors, more and better vaccines are required. The research stresses the worldwide influence of cancer and modern therapeutic approaches, such as vaccination. With advances in molecular and cellular biology, cancer therapeutic vaccination studies have been advanced; the discovery of tumor markers and advances in immunology and cancer therapies have changed. In contrast to chemotherapy and radiation, immunotherapy revolutionized treatment. The cancer therapeutic vaccines elicit antigen-specific T cell responses, helper T cell stimulation, and innate immune cells; the research indicates that these vaccines use various means to arouse the body’s defensive mechanism against cancer. Complex tools are explained by figures 1 and 2, which depict CD4+ T cells and innate immunity cells. Vaccines can be peptide/protein-based, whole-cell- or nucleic acid-based by application or clinical trial. Each category is looked at for its significant successes, triumphs, and failures: dendritic cell vaccines, the efficiency of antigen presentation, and clinical trial success. Cancer-therapeutic vaccines and immune checkpoint inhibitors are synergistic. Expanding the range of cancer vaccine antigens depends on finding added tumor-associated antigens and immunological checkpoints. However, there are flaws in cancer therapeutic vaccines, despite progress; tumor heterogeneity, immune evasion, and Safety are among concerns today. Recognizing these problems sets the stage for later chapters of optimization and new approaches.